5(x-4)-3(x-2)=12

Simple and best practice solution for 5(x-4)-3(x-2)=12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(x-4)-3(x-2)=12 equation:


Simplifying
5(x + -4) + -3(x + -2) = 12

Reorder the terms:
5(-4 + x) + -3(x + -2) = 12
(-4 * 5 + x * 5) + -3(x + -2) = 12
(-20 + 5x) + -3(x + -2) = 12

Reorder the terms:
-20 + 5x + -3(-2 + x) = 12
-20 + 5x + (-2 * -3 + x * -3) = 12
-20 + 5x + (6 + -3x) = 12

Reorder the terms:
-20 + 6 + 5x + -3x = 12

Combine like terms: -20 + 6 = -14
-14 + 5x + -3x = 12

Combine like terms: 5x + -3x = 2x
-14 + 2x = 12

Solving
-14 + 2x = 12

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '14' to each side of the equation.
-14 + 14 + 2x = 12 + 14

Combine like terms: -14 + 14 = 0
0 + 2x = 12 + 14
2x = 12 + 14

Combine like terms: 12 + 14 = 26
2x = 26

Divide each side by '2'.
x = 13

Simplifying
x = 13

See similar equations:

| 2a-17=21 | | 0.22(x+9)=0.2x+3.6 | | =(2x)(3x+1) | | -2w+8-2w=-w-7w+3w | | 0=(2x)(3x+1) | | 39.95+.35m=69.70 | | 2x+3x=2x-4 | | -8-(12-16)= | | 7a-(3a-4)=16 | | (-3)(2)(-1)(-3)= | | 6-c=16 | | -f+300=-65 | | x^2+3xy-8x-4y= | | 14(b-955)=616 | | F(10)=2x+5 | | 3+-7=4t+7 | | 2m-1=-6m+8 | | -2+10m-10=8(3m+4)-2 | | 49=3(x-3)+4x-1+2x+5 | | 24k=8(x+6) | | 3t^2-20t=-12 | | n=18+m | | 8.25c+12(55-c)=585 | | -5=7+3y | | 6x-13=83 | | 3+-7=4(t+7) | | x^2+x+120=0 | | 3x+50=275 | | -6(-6r+2)=-40+8r | | x+a^4=81a^4 | | F(n)=2n+2 | | 8d=7d-1 |

Equations solver categories